2019
DOI: 10.4168/aair.2019.11.5.677
|View full text |Cite
|
Sign up to set email alerts
|

Activated Leukocyte Cell Adhesion Molecule Modulates Th2 Immune Response in Atopic Dermatitis

Abstract: Purpose Activated leukocyte cell adhesion molecule (ALCAM), a member of the immunoglobulin superfamily, is highly expressed on dendritic cells. ALCAM and its receptor CD6 are co-stimulatory molecules in the immunological synapse; their interaction is required for T cell activation. While atopic dermatitis (AD) is recognized as a T helper 2 (Th2)-mediated allergic disease, the role of ALCAM in its pathogenesis is unclear. Methods ALCAM levels were measured in the serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The IgG4 monoclonal antibody dupilumab targets the interleukin-4 receptor alpha chain (IL-4Rα), thus inhibiting the biological effects of the cytokines IL-4 and IL-13 essential for the Th2 response. 1 2 3 We performed a prospective observational real-life study to evaluate the efficacy of dupilumab in patients with chronic rhinosinusitis with nasal polyps (CRSwNP) associated with moderate-to-severe atopic dermatitis (msAD).…”
mentioning
confidence: 99%
“…The IgG4 monoclonal antibody dupilumab targets the interleukin-4 receptor alpha chain (IL-4Rα), thus inhibiting the biological effects of the cytokines IL-4 and IL-13 essential for the Th2 response. 1 2 3 We performed a prospective observational real-life study to evaluate the efficacy of dupilumab in patients with chronic rhinosinusitis with nasal polyps (CRSwNP) associated with moderate-to-severe atopic dermatitis (msAD).…”
mentioning
confidence: 99%
“…AD is a multiplex disease that has a genetic predisposition combined with an immune response as well as environmental factors [71]. Previous studies documented that various animal models have been developed for the investigation of AD [72]. A study was conducted by Back et al [68] on a rat model; in this model, symptom development after weaning is followed by increases in the levels of serum IgE and skin NGF, IL-4, and IL-13 at approximately 3 weeks after injection [73].…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…An imiquimod-induced psoriasis model is used to imitate the symptoms of patients with psoriasis in the clinic ( 17 , 18 ). It has been reported that disturbances in the innate and adaptive cutaneous immune responses are responsible for the development and sustainment of psoriatic inflammation ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple pharmaceuticals could reduce cytokines and chemokines including histamine, TSLP, IL-5, IL-6, IL-8, and IL-13 to relieve the pruritus of the AD induced by DNFB ( 35 , 36 ). The levels of serum IgE, IL-4, and AD-involved cytokines, such as TNFα, interferon-γ (IFN-γ), IL-1β, TSLP, IL-33, and IL-25, also mediate inflammation in an oxazolone-induced mouse model ( 19 , 37 ). Different cytokines and chemokines, such as interleukin, TNFα, INFγ, and monocyte chemotactic protein 1 (MCP-1), also increased in imiquimod-induced psoriasis ( 38 , 39 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation